On the S-invariance property for S-flows - Saif, Amin; Kilicman, Adem (Hindawi Publishing Corporation, 2010)
We define an equivalence relation on a topological space which is acted by topological monoid S as a transformation semigroup. Then, we give some results about the S-invariant classes for this relation. We also provide a condition for the existence of relative S-invariant classes.